2014
DOI: 10.1016/j.toxrep.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Survival predictors in paraquat intoxification and role of immunosuppression

Abstract: Paraquat poisoning resulted in multiorgan failure and is associated with high mortality. We audited 83 historical cases of paraquat poisoning in past 2 years treated with conventional decontamination and supportive treatment, followed by enrolling 85 patients over a 2 year period into additional immunosuppression with intravenous (i.v.) methylprednisolone and i.v. cyclophosphamide.Our results showed that age, poor renal function and leucocytosis are the main predictors of fatal outcome. Immunosuppression regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Further, prevention of the inflammatory response and immune suppression has potential benefits in paraquat poisoning [2]. Hsin-Liang and coworkers confirmed that the presence of systemic inflammatory response was significantly associated with early mortality in paraquat poisoning [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, prevention of the inflammatory response and immune suppression has potential benefits in paraquat poisoning [2]. Hsin-Liang and coworkers confirmed that the presence of systemic inflammatory response was significantly associated with early mortality in paraquat poisoning [6].…”
Section: Discussionmentioning
confidence: 98%
“…This herbicide is one of the most common and active chemicals used in the Iranian agriculture [1]. Paraquat poisoning results in such multi-organ failures as pulmonary fibrosis, acute renal failure, and hepatic impairment, and is associated with high mortality [2]. Toxicological properties of paraquat are attributed to its ability to produce Reactive Oxygen Species (ROS), such as superoxide anion, which may directly or indirectly Use your device to scan and read the article online cause cell death [3].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory treatment with repeated pulse therapy of cyclophosphamide and methylprednisolone was reported to reduce the mortality rate in humans with severe paraquat poisoning [38]. More recently, intravenous cyclophosphamide and methylprednisolone were reported to be potential agents for improving patient survival [39]. Moreover, a methylprednisolone and dexamethasone combination has been used successfully in human clinical cases of paraquat intoxication [40].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, intravenous cyclophosphamide and methylprednisolone were reported to be potential agents for improving patient survival (Koh et al. 2014 ). Moreover, a methylprednisolone and dexamethasone combination has been used successfully in human clinical cases of paraquat intoxication (Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional approach in treating PQ poisoning focuses on three main areas, which include the prevention of absorption from the gastrointestinal tract, the enhancement of elimination of PQ from the body and the administration of therapies directed against toxicity. Nevertheless, these treatment methods have been disappointing, with very high mortality rates [1,[6][7][8][9]. Many studies have been conducted in an effort to search for an effective antidote for PQ poisoning with several being directed towards the use of antioxidants because PQ induces its toxic effect via oxidative stress-mediated mechanisms [10][11][12][13][14].…”
mentioning
confidence: 99%